The Integration of Islamic Philosophy of Science and Ethics in the Development of Modern Pharmacy: A Philosophical and Practical Review - Aulia Ishthofa Hanindita; Lingga Algifari; Fitrotun Husnia; Hafidz Rifai Pohan; Elsa Widya Lestari Br Sembiring (Solo International Collaboration and Publication of Social Sciences and Humanities, 2026)
Objective: This research is to explore the integration of Islamic philosophy of science and ethics in the development of modern pharmaceutical science that is sustainable, innovative, and by sharia principles. Theoretical framework: this research is based on the philosophy of Islamic science that balances revelation and reason as the basis for the development of knowledge, as well as Islamic ethics that emphasizes the principles of justice (al-adl), benefit (maslahah), and avoidance of harm (mafsadah) as a moral foundation in ensuring halal and thayyib pharmaceutical products. Literature review:  this study includes an analysis of 15 articles obtained from the Scopus, PubMed, and Google Scholar databases that discuss the integration of philosophy of science in modern science, the application of Islamic ethics in pharmaceutical practice, and the challenges and opportunities in the development of halal pharmaceuticals at the global level. Methods: This study uses a qualitative literature study approach with thematic analysis to identify the relevance and potential application of Islamic philosophy of science and ethics in modern pharmacy. Results: research shows that the integration of Islamic philosophy is able to provide a holistic framework of thinking that balances physical, mental, and spiritual aspects of pharmaceutical innovation. In addition, Islamic ethics play an important role in ensuring the halalness and quality of pharmaceutical products by the principles of thayyib. The research also identified challenges in the form of a lack of supporting regulations and health workers' understanding of Islamic principles, as well as a great opportunity that can be exploited, namely the increasing global demand for halal pharmaceutical products. Implications: This study emphasizes the importance of developing Sharia-based pharmaceutical policies and the need to integrate Islamic values into the pharmacy education curriculum to support the sustainability and excellence of the modern pharmaceutical system. Novelty: This research proposes the comprehensive integration of Islamic philosophy and Islamic ethics as a new approach to building a modern pharmaceutical system that is not only scientific but also moral, sustainable, and relevant to the needs of the global Muslim community.